Implementasi Marketing mix dan Relationship marketing pada PD Karya Bearing Motor, Bekasi - Heriyanti Heriyanti; Gillian Darmawaan (LITERATUS, 2021)
Companies in doing marketing need proper strategy so as to be firms operating in the fields of services of non-services develop and occupying a position is best to maximize resources. Marketing mix is marketing strategy used by PD Karya Bearing Motor in developing their business, covering product, price, place and promotion. The implementation of marketing mix and relationship marketing activity can support the development of each other all of the company business. In its implementation PD Karya Bearing Motor has implemented the mix marketing strategy in the marketing of spareparts motor vehicle although there are still not maximum such as the implementation of the high promotion only rely on word of mouth and system users online that has not yet been optimized used. In their relation marketing PD Karya Bearing Motor to provide the best service and supplies, the factors that must be taken care of by the company in relationship marketing is the belief, commitment, communication and the handling of conflict. These factors have applied. PD Karya Bearing Motor in enhancing good relations with customers. This methodology applied qualitative research methodology approach a case study. The purpose of this research is wanting to know how the implementation of marketing mix and relationship marketing at PD Karya Bearing Motor. The result is PD Karya Bearing Motor marketing continue to grow as proven from customers using the product PD Karya Bearing Motor already reached to Sulawesi, PD Karya Bearing Motor to provide Products and services tried to satisfy customers, In the hope of PD Karya Bearing Motor product can serve or reach the whole country and international.